Using J Notes To Improve Writing Ability In Narrative Text At Second Semester Of Universitas Bhinneka PGRI - Rakhmawati, Ika; Nugrahini, Yulia (Universitas Pahlawan Tuanku Tambusai, 2024)
Being able to read in English is very important as it is known that success in reading is the most necessary because it is a basic tool of education. Consequently, the concern of English learning is no longer on the acquisition of language components i.e. grammar, vocabulary, and sound system in isolation. The design of this research is a classroom action research with cycle model since this research is planned to improve the students’ writing ability at the second semester of Universitas Bhinneka PGRI using J Notes Application. From first cycle, it is known that amount of the students who passed the writing test increased. The result of the study on this cycle was 16 students passed the writing test. 73% of the students were successful. The result of second cycle was 19 students passed the writing test. 86% of the students were successful